QoS amendment toward seamless handover in network mobility NEMO - Hussien, Loay Faisal; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Zeki, Akram M. (Asian Research Publishing Network (ARPN), 2015)
Network Mobility Basic Support (NEMO BS) protocol is an extension of Mobile IPv6. It provides collective mobility for a bunch of nodes in vehicular area network. The standard NEMO BS (RFC 3963) protocol suffers from a number of limitations, such as inefficient routing and increased handover latency. Most previous studies attempted to solve such problems have imposed an extra signalling load. Therefore, the mechanism of proposed scheme is based on Fast Hierarchical Mobile IPv6, which enhances Mobile IPv6 by reducing the latency of address configuration and the homenetwork registration. In this paper, to achieve seamless handover and delivery of real-time traffic in mobile environment, Differentiated Service model is deployed in NEMO network. The QoS management is coupled with mobility management at the IP level. In order to evaluate QoS within Mobility environment, NS-2 has been used. The simulation results demonstrate that the proposed scheme is a valuable solution for promising NEMO applications.